1997
DOI: 10.5271/sjweh.187
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of epidemiologic studies of lung cancer in welders

Abstract: Original articles Scand J Work En viron Health 1997;23: 104-13 A meta-analysis of epidemiologic studies of lung cancer in welders Objective A meta-analysis of epidemiologic studies was carried out on lung cancer risk among shipyard, mild steel, and stainless steel welders, and the role of asbestos exposure and smoking was considered. Methods The meta-analysis consisted of calculating combined relative risks (RR) and their variances through a logarithm transformation of published RR values and a weighing usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 49 publications
8
51
0
2
Order By: Relevance
“…This finding is consistent with that of a Swedish study that indicated that welders exposed to high levels of chromium have a higher risk for cancer of the trachea, bronchus, and lung than welders exposed to low levels of chromium (2, 3) and those of several other studies (26). Furthermore, the finding is biologically highly plausible (25), and the association did not disappear when smoking and asbestos exposure was adjusted for in the survival analysis (6,18,22). To test the hypothesis of higher risk for stainless steel welders, it seemed the most sensible to compare all welders that had been welding with stainless steel alloys, with only mild steel welders, even though many stainless steel welders were also mild steel welders.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is consistent with that of a Swedish study that indicated that welders exposed to high levels of chromium have a higher risk for cancer of the trachea, bronchus, and lung than welders exposed to low levels of chromium (2, 3) and those of several other studies (26). Furthermore, the finding is biologically highly plausible (25), and the association did not disappear when smoking and asbestos exposure was adjusted for in the survival analysis (6,18,22). To test the hypothesis of higher risk for stainless steel welders, it seemed the most sensible to compare all welders that had been welding with stainless steel alloys, with only mild steel welders, even though many stainless steel welders were also mild steel welders.…”
Section: Discussionsupporting
confidence: 90%
“…The increased risk of lung cancer among mild steel welders is consistent with those found in a large number of earlier studies summarized in meta-analyses with updates (4,18,22). Earlier studies have found no clear indications that the risk is related to various measures of welding exposure (18).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Multiple epidemiology studies have reported an elevated risk for the development of lung cancer among welders (Hansen et al, 1996;Moulin, 1997;Becker, 1999), whereas others have not (Steenland et al, 1991;Hansen et al, 1996;Danielsen et al, 2000). Moreover, epidemiological studies have been unable to correlate the development of lung cancer solely with exposure to Cr-containing SS welding fume as compared to non-Cr-containing MS fume (Moulin et al, 1993;Langard, 1994;Moulin, 1997). However, in vitro genotoxicity studies demonstrated that Cr-containing SS, but not MS, welding fumes are mutagenic and induce DNA damage (Hedenstedt et al, 1977;Maxild et al, 1978).…”
Section: Welding Exposure and Health Effectsmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) has concluded that WFs were "possibly carcinogenic" to humans, despite the fact that the finding was based on limited evidence in humans and inadequate evidence in laboratory animals (IARC, 1990). Several epidemiology studies suggest exposure to WFs is associated with an increased incidence of lung cancer (Becker, 1999;Moulin 1997;Simonato et al, 1991). However, other studies have not observed this elevated risk Address correspondence to: James M. Antonini, Health Effects Laboratory Division, National Institute for Occupational Safety and Health, 1095 Willowdale Road (M/S 2015) Morgantown, WV 26505, USA; e-mail: jga6@cdc.gov * Denotes equal contribution to this work.…”
Section: Introductionmentioning
confidence: 99%